Petrography and geochemistry of upper cretaceous-eocene magmatism in the pichaihue area, neuquén province - Mateo FerNández Caso, P.M. (2011)
Magmatism related to the growth and migration of the Andean arc was developed from the 36°40'S to the 38°20'S latitude, in the northwestern sector of the Neuquén Province, by the end of the Mesozoic. Hypabyssal and extrusive facies, which outcrop in the Pichaihue area, were described based on petrologic studies. The first ones are composed of andesites that are emplaced as lacoliths, dikes or sills intruding the Mesozoic sedimentary sequences. In addition, basalts outcrops were recognized. The extrusive facies consist of breccia or massive lavas and little domes. The geochemistry reveals an arc-like calc-alkaline signature with a normal crust and trace-element patterns which suggest a similar source. Based on regional knowledge, three groups are proposed: Cerro Mocho dikes with Ti anomalies and higher Sm/Yb; extrusive facies of the Upper Cretaceous- Paleocene (Rivera Andesite); and the hypabyssal facies of thr Eocene (Colipilli Dikes). Finally, the occurrences of these rocks in this segment of the Andes indicate an important shift to the East of the Upper Cretaceous-Eocene volcanic arc that reveals its easternmost position.